2021
DOI: 10.7717/peerj.11863
|View full text |Cite
|
Sign up to set email alerts
|

Validity and usefulness of the student-athletes’ motivation toward sport and academics questionnaire: a Bayesian multilevel approach

Abstract: Background Reliable assessment and understanding of student-athletes’ motivation for dual careers are crucial to support their career development and transitions. The purpose of this research was to examine the validity and usefulness of the student-athletes’ motivation toward sport and academics questionnaire (SAMSAQ-PT) in the Brazilian higher education context. Four studies were performed. Methods In study one, conceptually and semantic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
(74 reference statements)
1
5
0
Order By: Relevance
“…However, the results of this study illustrated that SAMSAQ-KR is composed of a total of five factors: athletic motivation, academic motivation, career athletic motivation, academic achievement motivation, and learning outcome motivation. The results also confirmed that each country has unique socio-cultural contexts and different relationships between the academic and athletic environments in college sport ( Fortes et al, 2010 ; Lupo et al, 2017 ; Quinaud et al, 2021 ).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, the results of this study illustrated that SAMSAQ-KR is composed of a total of five factors: athletic motivation, academic motivation, career athletic motivation, academic achievement motivation, and learning outcome motivation. The results also confirmed that each country has unique socio-cultural contexts and different relationships between the academic and athletic environments in college sport ( Fortes et al, 2010 ; Lupo et al, 2017 ; Quinaud et al, 2021 ).…”
Section: Discussionsupporting
confidence: 66%
“…Compared to the previous cross-cultural studies that examined student-athletes’ motivation toward athletics and academics used SAMSAQ, the results of this study demonstrated that the SAMSAQ-KR version was characterized by a different factor structure compared to the versions followed by other countries. For example, most previous studies sustained the three-factor structure by utilizing the CFA ( Fortes et al, 2010 ; Guidotti et al, 2013 ; Lupo et al, 2015 ; Quinaud et al, 2021 ). However, the results of this study illustrated that SAMSAQ-KR is composed of a total of five factors: athletic motivation, academic motivation, career athletic motivation, academic achievement motivation, and learning outcome motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst athletes competing in championships managed by a sports federation or associations and being enrolled in a full-time high school or university degree could consider themselves student-athletes, different eligibility criteria are adopted to allow them to access institutionalised dual career services and provisions (Capranica and Guidotti, 2016 : European Commission, 2016 ; Sanchez-Pato et al, 2017 ). Furthermore, individual self-identity and motivation to combine academic and sports careers differ based on the athletic level, sports career perspectives, self-awareness, and personal values of the athletes, as well as the dual-career support from cultural backgrounds and contexts (Gaston-Gayles, 2005 ; Harrison et al, 2014 ; de Subijana et al, 2015 ; Lupo et al, 2015 ; Quinaud et al, 2021 ; Lee et al, 2022 ). Therefore, the initial identification of future sports and academic performances would be based on a thorough understanding of the most relevant determinants supporting dual career paths and preventing risks of sports or academic burnout and dropouts.…”
Section: The Responsibilities and Challenges In The Dual-career Micro...mentioning
confidence: 99%
“…Despite the advantages and new interest in this combined quantitative and qualitative analysis, this mixed-methods approach, particularly within a repeated measures design has been scarce when studying student-athletes (Guidotti et al, 2015; Ryba et al, 2017; Stambulova & Wylleman, 2015, 2019; Steele et al, 2020). In separate research studies, qualitative designs have provided a deeper understanding of the development of student-athletes’ perceptions (Steele et al, 2020), and quantitative methods have been recurrently used across different countries (Guidotti et al, 2015; Quinaud et al, 2019, 2021; Stambulova & Wylleman, 2019; Steele et al, 2020). The Baller Identity Measurement Scale (BIMS) has been used to examine student-athletes’ identities with a single instrument rather than through separate athletic identity and student identity measurement tools (Harrison et al, 2010).…”
Section: Introductionmentioning
confidence: 99%